Peran Guru Kelas Sebagai Pelaksana Bimbingan dan Konseling dalam Membantu Mengatasi Problem Peserta Didik di Madrasah Ibtidaiyah - Pravitasari, Dyah; Septikasari, Resti (FingeR: Journal of Elementary School, 2022)
The importance of guidance and counseling to students is aimed at helping students to overcome the problems of personal, social, and academic aspects. Guidance in elementary school emphasizes the importance of the teachers’ role in the guidance function. In the teacher system, the teachers have more time to recognize the students deeper, so having the opportunity to have relationships is more effective. The aim of this research was to know the suitability of the teachers’ role as a doer of guidance and counseling with services in schools. The types of this research were field research, qualitative, and the approach used was qualitative descriptive. The result of this research was the problem that happened to 1st-grade students, the lack of students' ability to adapt to the new social environment. In 3rd grade, the difficulty with reading and writing skills, boredom in studying, the habit of making noise in class, and fighting habits in the class. In 6th grade, truancy, lack of motivation in learning, and anxiety about facing the final examination. Preventing teachers to help overcome the problem of students was personal, social, and learning development services, and cooperation with parents. The implementation, so far the role of teachers in implementing guidance and counseling had not been implemented optimally in accordance with the guidelines for implementing guidance and counseling in school. This was due to the lack of knowledge about the implementation of guidance and counseling, the teachers were never given specific training and the guidance and counseling program was not regulated systematically and designedly in school.